A novel two-scale damage model for fatigue damage analysis of transition region between high- and low-cycle fatigue. (December 2017) - Tang, Jiaojiao; Hu, Weiping; Meng, Qingchun; Sun, Linlin; Zhan, Zhixin
Highlights: A novel two-scale damage model is proposed for fatigue analysis in transition region. Damages of inclusion and matrix in RVE are simultaneously calculated. The Eshelby solution is adopted to derive the elastic modulus of damaged RVE. The numerical implementation for the proposed damage model is presented. The calculated results agree well with the experimental data. Abstract: In this study, a continuum damage mechanics-based method combined with a novel two-scale meso-mechanical model was proposed for modelling the fatigue damage evolution in metals, within the transition region. A representative volume element (RVE) consisting of a matrix and a microscopic inclusion was introduced to establish the damage-coupled constitutive equations of the material experiencing fatigue in the transition region. The Eshelby solution was adopted to obtain the elastic modulus deterioration of the RVE by using the damaged matrix and the inclusion. The ductile damage model of Lemaitre was applied to describe the damage evolutions of the matrix and the inclusion. The parameters in the damage evolution equations were determined from the fatigue test data. Then, these parameters were directly applied to the fatigue damage analysis of the transition region. The numerical simulation was executed using ABAQUS software, and the predicted results were in accordance with the experimental data. The proposed method provides a novel perspective to illustrate the mechanism of damage evolution within the transition region.